Nilai Kerja Keras Tokoh Utama dalam Novel Dompet Ayah Sepatu Ibu dan Relevansinya sebagai Bahan Ajar Sastra di SMA - Nabila, Ma'unatun; Israhayu, Eko Sri (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
This study examines the value of the main character's hard work in the novel Dompet Ayah Sepatu Ibu by J.S. Khairen and its relevance as a literature teaching material in high school. The purpose of this study is to describe the value of hard work reflected through the main character, as well as describe its relevance to literary learning in high school. This research uses a type of qualitative descriptive research with a literary sociology approach. The data used in this study is in the form of words, phrases, clauses, sentences, and dialogue excerpts that describe the value of hard work with a data source in the form of the novel Dompet Ayah Sepatu Ibu by J.S. Khairen. The data collection technique used is a literature study technique. In this study, data analysis was carried out through three stages, namely data reduction, data presentation, and conclusion drawn. The results of this study show that there is a value of hard work reflected in the main character in the form of serious effort in doing work, being able to find solutions to the problems faced, and using all the abilities they have to complete the work. The value of hard work in the novel Dompet Ayah Sepatu Ibu by J.S. Khairen can be used as a literary teaching material to instill character values in students at the high school level. This value can be internalized into Indonesian learning in accordance with the Learning Outcomes phase F in the elements of reading and watching, namely students are able to appreciate fiction and non-fiction texts. Thus, this research can be used as an alternative teaching material to strengthen the character value of students through literary works